Neoantigen quality predicts immunoediting in survivors of pancreatic cancer - Łuksza, Marta; Sethna, Zachary M.; Rojas, Luis A.; Lihm, Jayon; Bravi, Barbara; Elhanati, Yuval; Soares, Kevin; Amisaki, Masataka; Dobrin, Anton; Hoyos, David; Guasp, Pablo; Zebboudj, Abderezak; et al. (Nature (London), 2022)
Cancer immunoediting 1 is a hallmark of cancer 2 that predicts that lymphocytes kill more immunogenic cancer cells to cause less immunogenic clones to dominate a population. Although proven in mice 1 , 3 , whether immunoediting occurs naturally in human cancers remains unclear. Here, to address this, we investigate how 70 human pancreatic cancers evolved over 10 years. We find that, despite having more time to accumulate mutations, rare long-term survivors of pancreatic cancer who have stronger T cell activity in primary tumours develop genetically less heterogeneous recurrent tumours with fewer immunogenic mutations (neoantigens). To quantify whether immunoediting underlies these observations, we infer that a neoantigen is immunogenic (high-quality) by two features—‘non-selfness’  based on neoantigen similarity to known antigens 4 , 5 , and ‘selfness’  based on the antigenic distance required for a neoantigen to differentially bind to the MHC or activate a T cell compared with its wild-type peptide. Using these features, we estimate cancer clone fitness as the aggregate cost of T cells recognizing high-quality neoantigens offset by gains from oncogenic mutations. With this model, we predict the clonal evolution of tumours to reveal that long-term survivors of pancreatic cancer develop recurrent tumours with fewer high-quality neoantigens. Thus, we submit evidence that that the human immune system naturally edits neoantigens. Furthermore, we present a model to predict how immune pressure induces cancer cell populations to evolve over time. More broadly, our results argue that the immune system fundamentally surveils host genetic changes to suppress cancer. The human immune system naturally edits cancers of high-quality neoantigens.